Phase engineering in nanocrystalline high-entropy alloy composites to achieve strength-plasticity synergy. (May 2023) - Wang, Junjie; Zhao, Ning; Yan, Mengyang; Kou, Zongde; Fu, Shu; Wu, Shangshu; Liu, Sinan; Lan, Si; You, Zesheng; Wang, Di; Hahn, Horst; Feng, Tao
Abstract: In this work, the strength-plasticity synergy of Al/CoCrFeNi nanocrystalline high-entropy alloy composite (nc-HEAC) prepared by laser-inert gas condensation is achieved via nanoscale diffusion induced phase transition (DIPT) process. The yield strength and elongation of the 16%-Al/CoCrFeNi nc-HEAC annealed at 900 °C were 1338 MPa and 12.1%, showing the combination of outstanding strength and considerable ductility. The synergy of multiple strengthening mechanisms were revealed. Driving the phase transition of nanocrystalline dual-phase composites by thermal diffusion establishes a novel phase engineering design strategy for high-performance alloys. Graphical abstract: Image, graphical abstract